Validation and reliability assessment of the mini-nutritional assessment-short form questionnaire among older adults in South India - Yuvaraj Krishnamoorthy; M Vijayageetha; Ganesh Kumar Saya (Wolters Kluwer Medknow Publications, 2021)
Background: Nutrition of the elderly affects immunity and functional ability and leads to increased morbidity and mortality. Validation of a short-form (SF) scale will make the assessment easier for primary care physicians. Hence, the study was done to assess the validity and reliability of Mini-Nutritional Assessment-SF (MNA-SF) Questionnaire among elderly in Puducherry. Methods: A cross-sectional study among 279 elderly was conducted in four villages of rural Puducherry. We have used three forms of MNA questionnaire. Diagnostic accuracy of the MNA-SF was assessed and internal consistency was interpreted using Cronbach's alpha. Results: The prevalence of malnutrition by the MNA full-form scale was 17.9%. Similar prevalence was reported by the body mass index (BMI) MNA-SF (16.5%), but calf-circumference (CC) MNA-SF overestimated the prevalence (38%). Sensitivity was higher in CC-MNA-SF (92%) when compared to BMI-MNA-SF (72%), while specificity was higher in BMI-MNA-SF (95.6%) when compared to CC-MNA-SF (73.8%). The positive predictive value was higher in BMI-MNA-SF (78.3%) when compared to CC-MNA-SF (43.4%), while the negative predictive value almost similar in both the scales. Reliability of the questionnaire showed the highest value for MNA full form (alpha = 0.71). Conclusion: This shows that both the forms of MNA-SF (BMI-based, CC-based) were valid and can be recommended as a screening tool for the assessment of nutritional status of the elderly.